Catalytic properties of dispersed iron oxides Fe2O3/MO2 (M = Zr, Ce, Ti and Si) for sulfuric acid decomposition reaction: Role of support. (4th January 2018) - Nadar, Ashish; Banerjee, Atindra Mohan; Pai, M.R.; Pai, R.V.; Meena, Sher Singh; Tewari, R.; Tripathi, A.K.
Abstract: Supported iron oxides have been established as an important class of catalyst for high temperature sulfuric acid decomposition. With an objective to elucidate the role of support in modifying the overall catalytic properties of dispersed iron oxide catalysts, a series of supported iron oxide based catalysts, Fe2 O3 (15 wt%)/MO2 (M = Zr, Ce, Ti and Si), synthesized by adsorption-equilibrium method, is investigated for sulfuric acid decomposition reaction. The structure of dispersed iron oxide phases largely depended on the nature of the support oxide as revealed by the XRD and Mössbauer studies. α-Fe2 O3 is found to be present as a major phase on ZrO2 and CeO2 support while ε-Fe2 O3 was the major phase on silica supported iron oxide. On the other hand, presence of mixed oxide Fe2 TiO5 was revealed over TiO2 support. Strong dispersed metal oxide-support interactions inhibited the total reduction of the dispersed phase on SiO2 and TiO2 as compared to complete reduction of dispersed iron oxide on CeO2 and ZrO2 supports during temperature programmed reduction upto 1000 °C. The order of catalytic activity at a temperature of ∼750 °C is observed as Fe2 O3 /SiO2  > Fe2 TiO5 /TiO2  > Fe2 O3 /ZrO2  > Fe2 O3 /CeO2, while at higher temperatures of ∼900 °C the SO2 yield is found to be comparable for all catalysts. A relationship between the rate of sulfate decomposition and catalytic activity is established through detailed TG-DTA investigations of sulfated catalyst and support. Considerable influence of the support oxide on the composition, structure, redox properties, morphology and catalytic activities of the active iron oxide dispersed phase has been observed. Thus, the support oxides operate as a critical component in the complex supported metal oxide catalysts and these findings might influence the design and development of future high temperature sulfuric acid decomposition catalysts. Graphical abstract: Highlights: Investigations on supported iron oxide catalysts for H2 SO4 decomposition. α-Fe2 O3 over ZrO2 and CeO2, ε-Fe2 O3 over SiO2, Fe2 TiO5 over TiO2 . Catalytic activity at 750 °C: Fe2 O3 /SiO2  > Fe2 TiO5 /TiO2  > Fe2 O3 /ZrO2  > Fe2 O3 /CeO2 . Probable mechanism proposed via thermal decomposition studies of sulfated catalyst. Support imparts significant influence on the catalytic properties.